2021
DOI: 10.3233/jad-200958
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ɛ4 (APOE ɛ4) Allele is Associated with Long Sleep Duration Among Elderly with Cognitive Impairment

Abstract: Background: Apolipoprotein E gene (APOE) ɛ4 allele increases the risk for Alzheimer’s disease (AD). Furthermore, among patients with cognitive impairment, longer sleep duration is associated with worse cognitive performance. To date, literature examining the associations between APOE ɛ4 allele and objective sleep duration is limited. Objective: Our aim was to assess the association between APOE ɛ4 and objective sleep duration, among patients with mild cognitive impairment (MCI) and AD. A sub-sample of 89 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…We propose that adopting a diet rich in vegetables and a physically active lifestyle, by lowering inflammation, could help reduce mortality and morbidity, including cognitive decline among elderly. Furthermore, given that long sleep seems to relate with inflammation levels, as well as cognition and disease severity among elders with cognitive decline [ 42 , 43 , 86 ], we and others have previously reported that treatment with sedative/sleep-prolonging psychotropic medication in this population should be given with caution [ 42 , 43 , 86 , 87 ]. These simple practical recommendations could be easily applied in a primary care setting.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that adopting a diet rich in vegetables and a physically active lifestyle, by lowering inflammation, could help reduce mortality and morbidity, including cognitive decline among elderly. Furthermore, given that long sleep seems to relate with inflammation levels, as well as cognition and disease severity among elders with cognitive decline [ 42 , 43 , 86 ], we and others have previously reported that treatment with sedative/sleep-prolonging psychotropic medication in this population should be given with caution [ 42 , 43 , 86 , 87 ]. These simple practical recommendations could be easily applied in a primary care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this might explain the markedly strong association between insomnia symptoms and cognitive performance in this high‐risk group, in which ongoing neurodegeneration processes in APOE ε4 allele carriers could lead to both impaired memory performance and insomnia symptoms. Previous studies have shown that APOE ε4 allele carriers presented with sleep characteristics consistent with insomnia (i.e., insomnia itself, shorter sleep duration, more awakenings, and self‐reported daytime and sleep disturbances), 45–48 although sleep disturbances of a different nature have been reported in carriers as well (i.e., longer sleep duration) 49 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that APOE ε4 allele carriers presented with sleep characteristics consistent with insomnia (i.e., insomnia itself, shorter sleep duration, more awakenings, and selfreported daytime and sleep disturbances), [45][46][47][48] although sleep disturbances of a different nature have been reported in carriers as well (i.e., longer sleep duration). 49 To our knowledge, only one previous study evaluated whether the APOE genotype interacts with insomnia to predict brain health outcomes. In cognitively healthy older adults, Grau-Rivera et al found that the presence of insomnia was associated with worse delayed memory recall in APOE ε4 carriers only, while in non-carriers, insomnia was associated with worse working memory.…”
Section: Moderating Effect Of Biomarkers Of Dementia Risk On the Asso...mentioning
confidence: 99%
“…17 Sleep disturbances, particularly sleeping longer, have been associated with more severe cognitive impairment and worse prognosis in individuals with MCI, 18 especially in APOέ4 carriers. 19 Reduced medial temporal lobe volume was shown to be related to sleep disturbances but no other psychiatric symptoms in older adults with MCI, 20 suggesting that sleep pattern could be a clinical biomarker of AD and a target for dementia risk reduction. In non-amnestic MCI, the relationship between sleep-wake disturbance and cognitive functioning could suggest shared neurobiological underpinnings.…”
Section: Neuropsychiatric Symptoms (Nps) In MCImentioning
confidence: 99%